The Age-Related Efficacy of Dimethyl Fumarate and Natalizumab in the Real-World Management of Multiple Sclerosis - Roberto De Masi; Stefania Orlando; Antonella De Donno (MDPI AG, 2021)
We investigated the comparative age-related efficacy of dimethyl fumarate (DMF) and natalizumab (NTZ) in clinical practice on multiple sclerosis (MS). Research in this area is lacking in the previous literature. In a three-year retrospective and clinical-paraclinical study, we compared 173 DMF patients and 94 NTZ patients with a similar average age (40 years) and disease duration (DD) (10 years). Expanded Disability Status Scale (EDSS) scores were higher in the NTZ group than in the DMF group at 3.5 vs. 2.5, respectively (p = 0.001). However, in both groups, age values correlated with DD (r = 0.42; p < 0.001), EDSS (r = 0.52; p < 0.001) and age at onset (r = 0.18; p < 0.001). Furthermore, age-adjusted Kaplan-Meier curves showed that NTZ-treated subjects maintained a 1.0-3.0 EDSS status score (p = 0.003) more frequently and a 3.5-7.0 score (p = 0.022) significantly less frequently compared with DMF-treated subjects. The EDSS percentage mean difference between NTZ and DMF groups was 81.6%, decreasing inversely with age (r = −0.34; p < 0.001). Finally, high EDSS score values were reached at the age of 39-40 years, regardless of their experimental group. We demonstrated age as a major contributor in disability and response to therapy in current management of MS. Thus, age should be considered in the risk/benefit evaluation in decision making for the disease modifying treatments in MS.